Analysis of the clinical and genetic characteristics of a Chinese family with osteogenesis imperfecta type I. Issue 9 (19th July 2022) - Niu, Zhijie; Lai, Yongjing; Zhou, Wenwen; Liu, Lingyuan; Tan, Songhua; He, Guangyao; Li, Jingyu; Tang, Fen; Su, Yupei; Xu, Yanglong; Liu, Lei; Xie, Lihong; et al.
Abstract: Background: Osteogenesis imperfecta type I (OI‐I) is a rare genetic disorder characterized by skeletal deformity, bone fragility, blue sclerae, dentinogenesis imperfecta, and hearing loss. The current study aimed to confirm the clinical diagnosis and genetic cause of OI‐I in a four‐generation Chinese family. Methods: Clinical investigation and pedigree analysis were conducted to characterize the phenotypic manifestations of a Chinese family with OI‐I. Follow‐up audiometry and imaging tests were used to evaluate the postoperative outcomes of stapes surgery in the proband with otosclerosis. Whole‐exome sequencing (WES) and Sanger sequencing were used to identify the pathogenic gene variants and for cosegregating analysis. Results: We described in detail the clinical features of the collected family with autosomal dominant OI‐I, and firstly identified a pathogenic splicing variant (c.2344‐1G>T) in intron 33 of COL1A1 in a Chinese family. The molecular analysis suggested that the mutation might cause splice site changes that result in a loss of gene function. The proband, who suffered from otosclerosis and presented two‐side middle‐severe conductive hearing loss, benefitted significantly from successive bilateral middle ear surgery. Conclusions: The diagnosis of OI‐I in a Chinese family was established by clinical and genetic investigation. A heterozygous pathogenic splicing variant in COL1A1 was directly responsible for the bone fragility and hearing loss of this family. Otosclerosis surgery should be suggested to rehabilitate conductive hearing impairment in OI patients. Abstract : 1. A heterozygous pathogenic splicing variant (c.2344‐1 G > A) was firstly identified in a four‐generation Chinese family with osteogenesis imperfecta type I. 2. The c.2344‐1 G > A COL1A1 mutation might cause splice site changes that result in a loss of gene function. 3. Otosclerosis surgery should be suggested to rehabilitate conductive hearing impairment in OI‐I patients.